Self-Assembled Nanotubes Based on Chiral H8-BINOL Modified with 1,2,3-Triazole to Recognize Bi3+ Efficiently by ICT Mechanism - Jisheng Tao; Fang Guo; Yue Sun; Xiaoxia Sun; Yu Hu (Micromachines, 2024)
A novel fluorescent “off” probe R-β-D-1 containing a 1,2,3-triazole moiety was obtained by the Click reaction with azidoglucose using H8-BINOL as a substrate, and the structure was characterized by 1H NMR and 13C NMR and ESI-MS analysis. The fluorescence properties of R-β-D-1 in methanol were investigated, and it was found that R-β-D-1 could be selectively fluorescently quenched by Bi3+ in the recognition of 19 metal ions and basic cations. The recognition process of Bi3+ by R-β-D-1 was also investigated by fluorescence spectroscopy, SEM, AFM, etc. The complex pattern of R-β-D-1 with Bi3+ was determined by Job’s curve as 1 + 1, and the binding constant Ka of R-β-D-1 and Bi3+ was valued by the Benesi–Hildebrand equation as 1.01 × 104 M−1, indicating that the binding force of R-β-D-1 and Bi3+ was medium. The lowest detection limit (LOD) of the self-assembled H8-BINOL derivative for Bi3+ was up to 0.065 µM. The mechanism for the recognition of Bi3+ by the sensor R-β-D-1 may be the intramolecular charge transfer effect (ICT), which was attributed to the fact that the N-3 of the triazole readily serves as an electron acceptor while the incorporation of Bi3+ serves as an electron donor, and the two readily undergo coordination leading to the quenching of fluorescence. The recognition mechanism and recognition site could be verified by DFT calculation and CDD (Charge Density Difference).